2001
DOI: 10.1074/jbc.c100512200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Angiotensin IV (AT4) Receptor Is the Enzyme Insulin-regulated Aminopeptidase

Abstract: Central infusion of angiotensin IV or its more stable analogues facilitates memory retention and retrieval in normal animals and reverses amnesia induced by scopolamine or by bilateral perforant pathway lesions. These peptides bind with high affinity and specificity to a novel binding site designated the angiotensin AT 4 receptor. Until now, the AT 4 receptor has eluded molecular characterization. Here we identify the AT 4 Central infusions of the hexapeptide VYIHPF (angiotensin IV, Ang IV) 1 or its more stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
366
1
6

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 421 publications
(378 citation statements)
references
References 26 publications
5
366
1
6
Order By: Relevance
“…The unique localization of the enzymes may suggest the biological functions of the oxytocinase subfamily to be strictly regulated. Indeed, it is getting evident that the enzymes belonging to this subfamily play important roles in the maintenance of homeostasis such as blood pressure regulation, angiogenesis, and maintenance of memory (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique localization of the enzymes may suggest the biological functions of the oxytocinase subfamily to be strictly regulated. Indeed, it is getting evident that the enzymes belonging to this subfamily play important roles in the maintenance of homeostasis such as blood pressure regulation, angiogenesis, and maintenance of memory (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that aminopeptidase A plays a role in the regulation of blood pressure by regulating the renin-angiotensin system in the brain (21). P-LAP/oxytocinase, which is also designated as insulin-regulated aminopeptidase, was shown to be the angiotensin IV receptor and may play a role in the memory retention and retrieval (22). Recently, we and others reported that A-LAP/ERAP1 is a final processing enzyme of the precursors of major histocompatibility complex (MHC) class I-presented antigenic peptides (9,16).…”
mentioning
confidence: 99%
“…AngIV binds to a specific receptor called AT 4 , which is widely expressed in the kidney, including endothelial cells and proximal as well as convoluted tubules. The AT 4 receptor, by protein purification and peptide sequencing, has been identified to be insulin-regulated aminopeptidase (11).…”
Section: Generation Of Angii and Other Peptidesmentioning
confidence: 99%
“…Indeed, telomeres progressively expand in human cell lines stably overexpressing tankyrase-1 tagged with a nuclear localization sequence (2). Besides binding to TRF1, the ANK domain of tankyrase-1 also binds to an angiotensin-4 receptor previously known as IRAP (insulin-responsive aminopeptidase) (3,4). IRAP is a recycling vesicular protein that is recruited to the cell surface by insulin signaling.…”
mentioning
confidence: 99%